Comparative Study of Experiential Marketing, Brand Image and Customer Loyalty on Starbucks - Farrell Farhan Zhafiri; Isni Andriana; Ahmad Maulana (JEMBATAN, 2022)
This study aims to find out a comparison of experiential marketing, brand image, customer loyalty between Starbucks Kambang Iwak and Palembang Indah Mall. The data used in this study were primary data, with a sample of 100 respondents using a non-probability sampling technique with a purposive sampling approach. The analytical techniques used in this study were descriptive analysis and Mann Whitney difference test using the SPSS 25 program. The results showed that there are differences in experiential marketing and customer loyalty between Starbuck Kambang Iwak and Starbucks Palembang Indah Mall while there is no difference in brand image between Starbuck Kambang Iwak and Starbucks Palembang Indah Mall.